PREPARING EARLY CHILDHOOD EDUCATION - THE HEALTH PERSPECTIVE. - Hamzah, Fathiiah (Proceeding International Seminar of Islamic Studies, 2023)
Islam is a way of life. Moulding a practising Muslim starts as early as once the mother is confirmed pregnant. Islamic Education is from the womb to the tomb. Surah Yusuf Surah Mariam of the holy Al-Qur’an is constantly read by the parent while the foetus is in utero. Around 120 days at the second trimester of pregnancy, the parent supplicate do’a for the coming child to be ‘Soleh’ or ‘Solehah’. Immediately after delivery, the new-born is being Azan is being read at the ears. Good Muslim name is given. During ‘Aqiqah’ religious leaders of the society perform ‘tahnik’, putting mashed date at the palate of the new-born, cut few of the new-born’s hair, chanting prayers for his/her future. During infancy, breast feeding is a must for 2 years Surah Al Baqarah verse 233. Apart from its nutritive value breastfeeding helps to meet the emotional needs of an individual using the 5 senses of sight, smell, hear, touch taste developing a stable personality. Parent should all the time be alert giving encouragement absolute observation to ensure proper growth development. This will help to facilitate Early Childhood Education.